The Qur’ānic character: Maryam Bint ʻImrān - Bahari, Che Amnah (Islamic Book Trust, 2023)
This writing deliberates on Maryam bint ʻImrān, of whom the Qur’ān has deliberated several times in a lively manner and even a sūrah having her name as its title. A ḥadīth of Prophetصلى الله عليه وسلم also states that Maryam was one of the chosen women of the world during her time. Many mufassirūn based on the verses of the Qur’ān and aḥādīth of the Prophetصلى الله عليه وسلم has clarified her excellent character. What are the types of characters? How do we ordinary people benefit from this oft-repeated character? How can we emulate it, and how can we make it relevant in today’s contact? This writing will refer to relevant tafāsir of the Qur’ān to seek clarification on Maryam’s character, providing action guides for Muslims of today to emulate good morals and good parenting.